O futuro da telefonia convencional e a ascensão da rede móvel no Brasil - Costa e Silva, Edelise Cristina Gasparetto da (2018)
The purpose of this research was to show the growth of the mobile telephony since the 90’s in Brasil, the decline of the conventional telephony, as well as to point the tendency for the use of data, on broadband and on mobile. This research also shows the preference of the user between the different types of telephony. For such pointing it was used specific literature and for the obtention of the user’s point of view, it was considered an exploratory research (survey). This research was done through a Google’s form and counted with the opinion of 75 people, from Curitiba and its region. People, that acts on different parts of the market, including telecommunications gave their opinion. The resulting data of this research was compiled on tables and graphics which helped to point and make clear the preference of the user for the mobile telephony, even with the reservations about the quality of the service.